Date palm fibre filled recycled ternary polymer blend composites with enhanced flame retardancy. (August 2017) - Zadeh, Khadija M.; Ponnamma, Deepalekshmi; Al Ali Al-Maadeed, Mariam
Abstract: Flammability of recycled polypropylene (PP)/low density polyethylene (LDPE)/high density polyethylene (HDPE) ternary blends containing date palm fibres is investigated in this study. Melt blending is used for the composite preparation and the palm fibres induce good mechanical strength to the blend composites. The effect of flame retardant magnesium hydroxide, is studied through the limiting oxygen index analysis and cone calorimeter studies. Morphology of the palm fibres in presence of fire retardant reveals interesting facts of base hydrolysis. Since the polymers used are recycled ones and the fibres are obtained from the date palm leaves, the whole composite manufactured stands as low cost, less energy consuming and environmental friendly. Though the flame retardant reduced the mechanical properties, the palm fibres strengthened the whole composite thus helping to achieve the flame retardancy and mechanical properties simultaneously. Flame retardancy is correlated with the thermal degradation and thermal conductivity of the blend fibre composites as well.